Manajemen Pengorganisasian Program Dauroh Al-Arabiyah - Islam, Nur Izzatul; Mufidah, Nuril; Karim, Abdul Malik (Borneo Journal of Language and Education, 2024)
The Arabic language course on university is an integral part of the educational program designed to improve students' Arabic language skills, so good program management is needed. This study describes the objectives of the Arabic language course on campus, the organizational structure, and the determination of the grouping of course participants. This research uses a descriptive qualitative approach. The subject of this research is Dauroh Al-Arabiyah at IAIN Madura, Indonesia, in 2024, with three groups and 36 students. Data were collected through interviews with the Scientific and Intellectual Division administrators, observation by reviewing and observing the program, and documentation. The data were processed to be analyzed using the Miles and Huberman model which includes adjusting, presenting, concluding, or verifying. The results of this study are that the purpose of the student Arabic language course is to create students who are skilled in communication using Arabic, understand the culture, and can contribute to a multicultural global environment. The organizational structure in the Dauroh program includes the head of the Arabic language study program, the study program student association and the intellectual and scientific division that hold and control the course. And the determination of student course groupings according to student interests and talents, namely Kitabah, Taqdimul Qishah, and Stair Groups.